Ten questions concerning human-building interaction research for improving the quality of life. (December 2022) - Becerik-Gerber, Burçin; Lucas, Gale; Aryal, Ashrant; Awada, Mohamad; Bergés, Mario; Billington, Sarah L; Boric-Lubecke, Olga; Ghahramani, Ali; Heydarian, Arsalan; Jazizadeh, Farrokh; Liu, Ruying; Zhu, Runhe; et al.
Abstract: This paper seeks to address ten questions that explore the burgeoning field of Human-Building Interaction (HBI), an interdisciplinary field that represents the next frontier in convergent research and innovation to enable the dynamic interplay of human and building interactional intelligence. The field of HBI builds on several existing efforts in historically separate research fields/communities and aims to understand how buildings affect human outcomes and experiences, as well as how humans interact with, adapt to, and affect the built environment and its systems, to support buildings that can learn, enable adaptation, and evolve at different scales to improve the quality-of-life of its users while optimizing resource usage and service availability. Questions were developed by a diverse group of researchers with backgrounds in design, engineering, computer science, social science, and health science. Answers to these questions draw conclusions from what has been achieved to date as reported in the available literature and establish a foundation for future HBI research. This paper aims to encourage interdisciplinary collaborations in HBI research to change the way people interact with and perceive technology within the context of buildings and inform the design, construction, and operation of next-generation, intelligent built environments. In doing so, HBI research can realize a myriad of benefits for human users, including improved productivity, health, cognition, convenience, and comfort, all of which are essential to societal well-being. Highlights: The field of Human-Building Interaction (HBI) is defined. HBI stakeholders, goals and benefits and outcomes are discussed. The three dimensions, human, building, and interaction dimensions are explained. Enabling technology and scalability of HBI are provided. Opportunities and challenges for HBI research are discussed.